2018
DOI: 10.1155/2018/3037498
|View full text |Cite
|
Sign up to set email alerts
|

Pottery Sand as Fine Aggregate for Preparing Alkali‐Activated Slag Mortar

Abstract: Alkali-activated slag (AAS) mortars were prepared using pottery sand as a fine aggregate in a ratio of 1 : 1.75 using a blend of sodium silicate and NaOH as an alkaline activator at room temperature. e effects of sodium oxide content and silicate moduli on the setting time, fluidity, consistency, compressive strength, and drying shrinkage of different AAS mortars were determined. ese results revealed that sodium oxide content and silicate modulus had little effect on the setting time and workability of the mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…It is worth noting that Wang et al [15] have reported that the slump, slump flow, and setting time of an AASC cannot be tested as its viscosity is too high and it exhibits no plasticity when the liquid-solid ratio is 0.45. Therefore, the setting time and slump of the AASC were not tested; values for the setting time and fluidity of AAS mortars can be found in Reference [12].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is worth noting that Wang et al [15] have reported that the slump, slump flow, and setting time of an AASC cannot be tested as its viscosity is too high and it exhibits no plasticity when the liquid-solid ratio is 0.45. Therefore, the setting time and slump of the AASC were not tested; values for the setting time and fluidity of AAS mortars can be found in Reference [12].…”
Section: Resultsmentioning
confidence: 99%
“…The observed density of the pore structure of AASC provides a great deal of its strength. Previously, the authors of Reference [12] indicated that the pore size distribution of alkali-activated slag mortars included three ranges (<50 nm, 50-10,000 nm, >10,000 nm) within which the pore structure <50 nm played a significant role in the drying shrinkage: the higher the volume of pores <50 nm, the greater was the drying shrinkage resulting from the higher contracting stress influenced by the finer capillary pores [53].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mix proportion of the crushed AASCM aggregate and AASCM paste of specimens was the same as that of the block and mortar. The mix proportions of the block and mortar were adjusted according to that of the alkali-activated slag ceramsite concrete and alkali-activated slag mortar with pottery sand, as reported by Zhu et al (2018a, 2018b, 2019). The specimens were constructed by staggering five layers of main blocks and auxiliary blocks.…”
Section: Materials and Experimentsmentioning
confidence: 99%